Respuestas

2012-06-23T06:50:07+02:00

comensemos:

 

PARTE 1

 

a)  A(-3,4) B(1,2)

     

Distancia=((-3-1)^2+(4-2)^2)^(1/2) 

Distancia=((-4)^2+(2)^2)^(1/2)

Distancia=(16+4)^(1/2)

Distancia=(20)^(1/2)

Distancia=2*5^(1/2)  ------>  2*raiz(5)

 

b)  B(-5,3) A(4,1)

 

Distancia=((-5-4)^2+(3-1)^2)^(1/2) 

Distancia=((-9)^2+(2)^2)^(1/2)

Distancia=(81+4)^(1/2)

Distancia=(85)^(1/2)

 

c)  A(6,-3) B(1,4)

 

Distancia=((6-1)^2+(-3-4)^2)^(1/2) 

Distancia=((5)^2+(-7)^2)^(1/2)

Distancia=(25+49)^(1/2)

Distancia=(74)^(1/2)

 

PARTE 2

 

a)   A(-3,4) B(1,2)

 

m =  4-2 

      -3-2

 

m =  2 

      -5

 

m=-2/5

 

b)   B(-5,3) B(4,-1)

 

m =  3-(-1) 

        -5-4

 

m =  4 

      -9

 

m=-4/9

 

c)   A(6,-3) B(1,4)

 

m = -3-4 

        6-1

 

m =  -7 

        5

 

m=-7/5

 

un gusto ....=D